How police officers juggle work, a life partner, and kids - Granholm Valmari, Elin; Nygren, Ulla; Ghazinour, Mehdi; Gilenstam, Kajsa (Frontiers in Psychology, 2023)
Police officers frequently encounter stressful social situations during their working days. Furthermore, previous research on policing and families show that police officers’ families are impacted in different ways when at least one member of the family has the role of a police officer. Despite work spilling over to family life there is currently little research on police officers' role-balancing. Thus, the purpose of this study was to explore and describe the challenges that arise at the intersection between police officers' professional roles and their private life roles as parents and life partners, as well as how police officers balance these roles in between. We used qualitative content analysis after interviewing 13 uniformed police officers. The findings show how the police officers’ professional roles affect their private life roles within three different sub-themes and are summarized under the theme of ‘Balancing conflicting roles: Coping with professional and private life commitments’. The theme revolves around the various challenges of working as a uniformed police officer, such as hypervigilance and risks, as well as the enrichments and conflicts of working shifts while also juggling private life roles. The results also touch on gender and equality in life-partner relationships. The study raises an important question about how these challenges can be mitigated within Police authorities to enable uniformed police officers to balance their professional and personal lives in a healthy and sustainable manner.